Dampak Komitmen Organisasi Dan Etos Kerja Terhadap Kinerja Karyawan (Studi Kasus PT PLN (Persero) Painan) - Zusmawati Zusmawati; Ari Julianti (Universitas 45 Surabaya, 2023)
The purpose of this study was to analyze the impact of organizational commitment on the performance of employees of PT PLN company. Data collection was carried out by distributing questionnaires to 50 respondents using a saturated sampling technique, in which all members of the population were sampled, using multiple linear regression testing with the help of the SPSS application. The results of the study show that personality has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance